The Regional Subsystem Concept: From Heterogeneity to Pluralism - N. S. Labutkin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The study of regional subsystems dates back to the 1950s, when it became clear that the models developed to explain the logic behind the bipolar international system could not adequately reﬂect the speciﬁcities of regional processes. Therefore, there was a pressing need to complement traditional system level analysis with a new, subsystemic approach. The paper provides a comparative analysis of both Russian and Western deﬁnitions of the regional subsystem concept. The author examines the evolution of the regional subsystem concept research ﬁeld, its current state and identiﬁes the key competing approaches, as well as their methodological and theoretical foundations. The ﬁrst section covers deﬁnitions of the subsystem concept developed by the Western researchers during the Cold War period. The author emphasizes that this initial foundational phase for the development of the research ﬁeld was marked by extreme heterogeneity of views, opinions and assessments. The experts suggested various principles and criteria for identifying regional subsystems, while the very meaning of a ‘regional subsystem’ has not yet been settled. At the same time, the author shows that all the discussions during that period revolved around one central issue that is how the regional subsystem is linked to the ‘dominant’ one — a bipolar. In that regard, it is only natural that with the end of the Cold War the studies of regional subsystems faced new challenges but also gained a new momentum. The second section examines views of contemporary Russian and Western scholars. The author identiﬁes the key discussion points, which include primarily the nature of relations between subsystem actors: whether they should necessarily be cooperative or not; if they need formal institutionalization and whether they should be organized hierarchically with a strong leading state. The author concludes that despite the absence of expert consensus on these issues, the studies of regional subsystems have come a long way from extreme heterogeneity, even fragmentation of the very basic theoretical premises, to a much greater terminological consistency but have retained the pluralism of views, opinions and assessments.